Synthesis and research of biological properties of s-derivatives of 4-amino-5-(5-r-pyrazol-3-yl)-1,2,4-triazol-3-thiol - Fedotov, S. O.; Gotsulya, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (My University, 2021)
Bibliographic search includes antimicrobial, anti-fungal, anti-TB, antioxidant, anti-inflammatory, anxiolytic, fungicidal and other activities. The synthesis of substances that will contain in their structure simultaneously two pharmacophore fragments (pyrazole and triazole), will allow to obtain a number of potentially biologically active substances that could be used in medicine and pharmacy. For the above reasons, this area of work is relevant and practically significant.